Development of High-Protein Bar Incorporated with Moringa Oleifera Flower - Subramaniam, Sanggary; Hatijah Basri (Enhanced Knowledge in Sciences and Technology, 2024)
A protein bar is essentially a supplement bar that provides an excellent way to increase protein intake. The aim of this study was to formulate high-protein bars by using organic ingredients in different proportions. Three formulations of high-protein organic bars were developed with base ingredients of dates (64 g), apricots (16 g), whey protein concentrate (12 g) and cheddar cheese (8 g) of same proportions. Control bar (F1) consisted of only rice flour (15 g) without addition of chickpea flour and moringa flower powder as protein sources. F2 consisted of chickpea, rice flour and moringa flower powder in 5g each while F3 consisted of chickpea (2.5 g), rice flour (2.5 g) and moringa flower powder (10 g). The control and formulated protein bars were analysed in terms of physical, physicochemical and sensory properties. From the current study, the protein content ranged from 3.88 to 11.47 % among the formulated and commercial bars, in which F3 had the highest protein content among the formulated bars. Protein content for all the protein bars is shown to be non-significant with an F-value of 0.01 and a P-value of 0.99 (>0.05). Also, moisture content for all the protein bars is shown to be significant with an F-value of 11.4909 and a P-value of 0.0089 (<0.0500) in which F2 had the highest moisture content. In terms of texture, hardness for the control and formulated the protein bars is shown to be non-significant with an F-value of 0.1715 and a P-value of 0.8464 (>0.0500) whereas springiness for all the protein bars is shown to be non-significant with an F-value of 1.5864 and a P-value of 0.2798 (>0.0500). It was also observed that the water activity for the control and formulated the protein bars is shown to be significant with an F-value of 28 and a P-value of 0.001 (<0.05). Subsequently, pH for the control and formulated the protein bars is shown to be significant with an F-value of 22.75 and a P-value of 0.001 (<0.05). Results show that the sensory attributes for taste, aroma, texture, colour and overall acceptability were non-significantly higher (p>0.05) in F3 (code 054). It was concluded that moringa flower powder and chickpea flour are good protein sources to be added without affecting the sensory attributes, textural attributes, moisture content, water activity and pH. In future studies, the amount of moringa flower powder added during the development of the bars should be examined to increase protein content in the bar.